Chitosan-based magnetic bioadsorbent beads from eucalyptus sawdust waste for the Direct Violet-51 dye remediation: Eco-friendly strategy and statistical optimization - Oliveira, Rhayza Victoria Matos; Maia, Hermógenes Bezerra; Costa, José Arnaldo Santana [UNESP]; Romão, Luciane Pimenta Cruz [UNESP] (Elsevier, 2024)
In the present study, a new application was proposed for the eucalyptus sawdust waste, which is an environmental passive. Three adsorbent materials composed of chitosan (CS), sawdust (CSW), and magnetic beads (CSWF) were developed and used for the Direct Violet-51 remediation. The adsorption testes were optimized based on the variation of the adsorption parameters: (i) pH (2−12), (ii) contact time (5–60 min), (iii) initial dye concentration (10–60 mg L−1), (iv) adsorbent mass (10–100 mg) in 10 mL. The optimized conditions of the adsorption essays showed that the three synthesized adsorbents completely removed the dye from the aqueous medium, but under different experimental conditions. As the main findings in this study, we can highlight the excellent performance of CSW adsorbent material, which promoted maximum removal efficiency of Direct Violet-51 at neutral pH, which is of great importance for the industrial processes. On the other hand, CS and CSWF adsorbent materials exhibited a maximum adsorption efficiency at pH 2. Furthermore, the adsorbent materials were applied in the dye remediation in environmental water samples from the tap water, Marcela dam, and Poxim River, they did not suffer any major matrix interference, whose removal efficiency values varied between 99.8 and 100, 70.7–100, and 98.8–99.5 % for the CS, CSW, and CSWF, respectively. Finally, besides being materials produced from the waste, they can be reused more times, fitting into the concept of circular economy.
Keywords: Adsorption technology; Dye remediation; Environmental risk assessment; Waste reduction